CThrelfall_DATA_Nest_Predation_2010 - Threlfall, Caragh; Law, Bradley; Banks, Peter B. (Dryad Digital Repository, 2013)
Raw data collected in the field from a nest predation experiment. The metadata tab describes more detail about when and how the data was collected.